Trophic niche partitioning among non‐native fsh species coexisting in a Colombian high Andean reservoir (2024)
ABSTRACT: The introduction of non-native species to a new environment poses a threat to local biologi- cal diversity, causing instability in the functioning of the ecosystem. The ecological efects caused by these species have been scarcely documented in the Magdalena basin. By studying predator–prey interactions, we characterized the trophic niche of three non-native species (Cyprinus carpio, Micropterus salmoides, and Oncorhynchus mykiss) that dominate a high Andean reservoir in the Magdalena basin. This study allows us to understand their specifc feeding behaviors and how these behaviors facilitate their establishment in the reservoir. We evaluated the diversity of the prey they consume, their feeding strategy, and possible diferences in the feeding scheme. Forty individualswere analyzed, with the highest representation of M. salmoides with 17 individuals, followed by C. carpio (13 individuals), and fnally O. mykiss with 10 individuals. We identifed twenty categories of food as prey for these species, with aquatic invertebrates and vegetation material being the predominant prey. The analysis of stomach contents in these samples suggested that they are representative for determining specialized or generalist feeding strategies. There were no diferences in the number of prey items consumed by these three species. The analysis revealed that the feeding strategies are specifc for each species. There was no overlap in the diet of C. carpio with the other two species, however, the composition of the diet is similar between M. salmoides and O. mykiss. Analyzing the diet of these non-native fshprovides a useful tool for describing trophic interac- tions in this aquatic environment. Our results contribute information on the existing interactions amongst non-native species in the Magdalena basin, which is important for the development of strategies to manage and mitigate their impact.